Doping modification method of hafnium oxide-based dielectric film
By performing doping modification in the Zr-layer of the hafnium-based stacking system, the transition barrier between the polarized phase and the non-polarized phase is reduced by utilizing the doping modification of oxygen vacancy migration and charge balance effects, the problems of dielectric constant and leakage current in the hafnium-based system are solved, and higher dielectric performance and lower leakage current are achieved.
Patent Information
- Application Number
- CN202510020157.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-07
AI Technical Summary
In hafnium-based systems, how to achieve higher dielectric constants and lower leakage currents at operating voltages remains a key challenge.
By performing doping modification in the Zr-layer of the hafnium-based stacking system, leakage is suppressed using the limited oxygen vacancy migration and charge balance effects in the stacking system, while reducing the transition barrier between polarized o-phase and non-polarized t-phase, achieving higher dielectric performance.
The higher dielectric constant and lower leakage performance of the hafnium-based stacked system under 3D integration are achieved, improving the dielectric performance of the material and reducing leakage current.
Smart Images

Figure CN119833469A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dielectric material modification, and in particular relates to a doping modification method for a hafnium oxide-based dielectric film. Background Art
[0002] As device size continues to shrink, the transition to three-dimensional (3D) dynamic random access memory (DRAM) is particularly critical. One of the most important technology drivers is the use of dielectric materials with high dielectric constant (k) and low leakage. 2 The system has been widely used in the industry due to its compatibility with CMOS processes and mature atomic layer deposition (ALD) technology. However, a higher dielectric constant is still required to store enough charge for further 3D integration.
[0003] In recent years, the behavior of morphotropic phase boundary (MPB) has attracted extensive attention due to its high dielectric constant. In hafnium-based systems, MPB is attributed to the mutual transformation between the polar orthorhombic phase (o phase) and the non-polar tetragonal phase (t phase), and the prerequisite for the realization of MPB is a low transition barrier between the o phase and the t phase. Studies have shown that in HfO 2 Doping in the system is an effective method to achieve MPB. By adjusting the ratio of Hf / Zr, x Zr 1-x O 2 The k value can be increased to ~50 in thin films. Recently, researchers have proposed to increase the k value to ~50 by 0.5 Zr 0.5 O 2 Further doping of Al (~68) and La (~58) in (HZO) can achieve a higher dielectric constant. However, the higher leakage current (1E-5A / cm 2 ) limits its further development. So far, how to achieve higher k value and lower leakage current in hafnium-based systems remains a key challenge.
[0004] Previous studies have found that HfO 2 -ZrO 2 In the stacked system, the diffusion barrier of oxygen vacancies in the Hf layer is large, which limits the vertical migration of oxygen vacancies, thereby reducing leakage current and improving device durability. Therefore, a doping modification method to achieve higher k value and lower leakage in the stacked system has become an urgent problem to be solved in the prior art. Summary of the invention
[0005] The purpose of the present invention is to provide a doping modification method for hafnium oxide-based dielectric films, in which the Zr-layer is doped and modified in a hafnium-based stacking system. On the one hand, the restricted oxygen vacancy migration and charge balance effect in the stacking system are utilized to suppress leakage, and on the other hand, the transition barrier between the polarized o phase and the non-polarized t phase is reduced by doping, thereby achieving the higher k and lower leakage performance requirements of the hafnium-based stacking system under 3D integration.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] The present invention provides a doping modification method for a hafnium oxide-based dielectric film, comprising: doping and modifying a Zr-layer in a hafnium-based stacking system, on the one hand, utilizing the restricted oxygen vacancy migration and charge balance effect in the stacking system to suppress leakage, and on the other hand, reducing the transition barrier between a polarized o phase and a non-polarized t phase by doping, thereby realizing a hafnium-based stacking system under 3D integration.
[0008] Preferably, the hafnium oxide-based dielectric film is a hafnium-based stacked layer system, including: a film thickness of 4 to 10 nm.
[0009] Preferably, HfO 2 layer and ZrO 2 The thickness of the layers is 0.5 to 2 nm.
[0010] Preferably, the doping position of the doping element is the Zr-layer of the stacked layer system.
[0011] Preferably, the doping element is selected from one or more of Al, Ga, In, Sc, Y, La, Mg, Ca, and Sr.
[0012] Preferably, the doping concentration of the doping element is 2%-8%.
[0013] Preferably, the doping element is selected from one or more of Al, Y, La and Sr.
[0014] More preferably, the doping element is Y.
[0015] Compared with the prior art, the hafnium-based stacked system provided by the present invention achieves higher k and lower leakage through doping, and has the following beneficial effects:
[0016] 1) Doping the Zr-layer in the hafnium-based stacking system can keep the Hf-layer system as large as possible and suppress leakage.
[0017] 2) Oxygen vacancies are easily induced in the hafnium-based stacked system under trivalent or divalent doping, presenting a charge-balanced configuration. At the same time, the phase transition barrier between the o-phase and the t-phase becomes lower, making it easy to achieve MPB and thus improve the dielectric properties of the material.
[0018] 3) Under the charge balance effect, the oxygen vacancy defect state tends to merge with the bottom of the conduction band, passivating the original oxygen vacancy defect state and reducing leakage.
[0019] 4) The charge balance doping metal method of the present invention selects Al, Ga, In, Sc, Y, La, Mg, Ca and Sr through theoretical calculation and actual material screening. The above materials can achieve the beneficial effects of 1) to 3) above after theoretical verification. When the metal dopant is Al, Y, La and Sr, the above effects of increasing the k value and reducing leakage are more obvious. Comprehensively considering the influence of the charge balance effect of the above doping elements on the phase transition barrier and band structure, its E o-t (the potential barrier from the o phase to the t phase) and E t-o The barrier from the t-phase to the o-phase is very small, which is conducive to the formation of more MPB regions, which can improve the k value of the doping system and show better dielectric properties. At the same time, the oxygen vacancy defect state induced by doping can be passivated in the charge balance state to achieve a large band gap, thereby suppressing the leakage current. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 HfO in the embodiment 2 -ZrO 2 Schematic diagram of the stacked superlattice structure; 1 is ZrO 2 Layer 2: HfO 2 layer; the structure on the left is o phase; the structure on the right is t phase; the thickness of the layers is 1.0 nm.
[0021] Figure 2 Schematic diagram comparing the transformation barriers of the polarized o-phase and the non-polarized t-phase in the charge-balanced doping system in Examples 1 to 6; 3 is the potential barrier for the transformation from the o-phase to the t-phase, and 4 is the potential barrier for the transformation from the t-phase to the o-phase; the light gray dotted line is the potential barrier for the transformation from the o-phase to the t-phase in the undoped system, and the dark gray dotted line is the potential barrier for the transformation from the t-phase to the o-phase in the undoped system.
[0022] Figure 3 Schematic diagram of the band gap width under the charge balance effect in Examples 1 to 6; 5 is the o-phase, 6 is the t-phase; the light gray dotted line is the o-phase band gap of the undoped system, and the dark gray dotted line is the t-phase band gap of the undoped system. DETAILED DESCRIPTION
[0023] In order to more fully understand and demonstrate the technical solutions, purposes and advantages of the present invention, the technical effects produced by the present invention are further described in detail and completely in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all. It should be pointed out that for those of ordinary skill in the art, other embodiments obtained without departing from the concept of the present invention all belong to the protection scope of the present invention.
[0024] The calculation method used in the following embodiments is a first-principles calculation based on density functional theory, and the calculation software package used is the PWmat calculation software package, but is not limited to this. There are also VASP, CASTEP, Gauss, Wien2k, etc. The PWmat software is a first-principles calculation software package based on GPU acceleration, and it also provides most elements in the periodic table, and is highly practical.
[0025] Example 1
[0026] In this embodiment, the superlattice ferroelectric thin film is HfO 2 -ZrO 2 , used to provide the doped metal as Al, the specific method is as follows:
[0027] For Al in HfO 2 -ZrO 2 The formation energy of oxygen vacancies in HfO was calculated. When the concentration of Al element and oxygen vacancies was 2:1, the formation energy was negative, indicating that this configuration was more likely to form, indicating the charge balance effect. 2 -ZrO 2 Al is implanted into the film. 2 -ZrO 2 The performance prediction of the phase transition barrier and band structure was carried out in the experiment. The results showed that the mutual transition barriers of ot were reduced, and the barrier of the transformation from o phase to t phase was greater than that of the transformation from t phase to o phase. In addition, compared with the intrinsic system, the band gap width was slightly reduced, but no deep energy level defects appeared. In this embodiment, Al was used as HfO 2 -ZrO 2 Doping with metal can reduce the ot phase transition barrier, thereby promoting the formation of more MPB regions. Secondly, the charge balance effect passivates the defect states caused by oxygen vacancies, achieving a larger band gap and reducing leakage current, confirming that Al doping can significantly promote the formation of MPB and reduce leakage current.
[0028] Example 2
[0029] In this embodiment, the superlattice ferroelectric thin film is HfO 2 -ZrO 2, the metal used for doping is Ga, and the specific implementation method is as follows:
[0030] For Ga in HfO 2 -ZrO 2 The formation energy of oxygen vacancies in HfO was calculated. When the concentration of Ga element and oxygen vacancies was 2:1, the formation energy was negative, indicating that this configuration was more likely to form, indicating the charge balance effect. 2 -ZrO 2 Ga is implanted into the film. 2 -ZrO 2 The performance prediction of the phase transition barrier and band structure was carried out. The results showed that the mutual transition barrier of ot was reduced, and the barrier of the transformation of o phase to t phase was greater than that of the transformation of t phase to o phase. In addition, compared with the intrinsic system, the band gap width was slightly reduced, but no deep energy level defects appeared. In this embodiment, Ga was used as HfO 2 -ZrO 2 Doping with metal can reduce the ot phase transition barrier, thereby promoting the formation of more MPB regions. Secondly, the charge balance effect passivates the defect states caused by oxygen vacancies, achieving a larger band gap and reducing leakage current, confirming that Ga doping can significantly promote the formation of MPB and reduce leakage current.
[0031] Example 3
[0032] In this embodiment, the superlattice ferroelectric thin film is HfO 2 -ZrO 2 , the metal used to provide the doping is In, and the specific implementation method is as follows:
[0033] For In in HfO 2 -ZrO 2 The formation energy of oxygen vacancies in HfO was calculated. When the concentration of In element and oxygen vacancies was 2:1, the formation energy was negative, indicating that this configuration was more likely to form, indicating the charge balance effect. 2 -ZrO 2 In is implanted into the film. 2 -ZrO 2 The performance prediction of the phase transition barrier and band structure was carried out in the paper. The results show that the mutual transition barrier of ot is reduced, and the barrier of the transformation of o phase to t phase is larger than that of the transformation of t phase to o phase. In addition, compared with the intrinsic system, the band gap width is slightly reduced, but no deep energy level defects appear. In this embodiment, In is used as HfO 2 -ZrO 2Doping with metal can reduce the ot phase transition barrier, thereby promoting the formation of more MPB regions. Secondly, the charge balance effect passivates the defect states caused by oxygen vacancies, achieving a larger band gap and reducing leakage current, confirming that In doping can significantly promote the formation of MPB and reduce leakage current.
[0034] Example 4
[0035] In this embodiment, the superlattice ferroelectric thin film is HfO 2 -ZrO 2 , the metal used to provide doping is Sc, and the specific implementation method is as follows:
[0036] For Sc in HfO 2 -ZrO 2 The formation energy of oxygen vacancies in HfO was calculated. When the concentration of Sc element and oxygen vacancies was 2:1, the formation energy was negative, indicating that this configuration was more likely to form, indicating the charge balance effect. 2 -ZrO 2 Sc element was injected into the film. The results showed that the mutual transformation barriers of ot were reduced, and the barrier of transformation from o phase to t phase was greater than that of transformation from t phase to o phase. In addition, compared with the intrinsic system, the band gap width was slightly reduced, but no deep energy level defects appeared. In this embodiment, Sc was used as HfO 2 -ZrO 2 Doping with metal can reduce the ot phase transition barrier, thereby promoting the formation of more MPB regions. Secondly, the charge balance effect passivates the defect states caused by oxygen vacancies, achieving a larger band gap and reducing the leakage current, confirming that Sc doping can significantly promote the formation of MPB and reduce the leakage current.
[0037] Example 5
[0038] In this embodiment, the superlattice ferroelectric thin film is HfO 2 -ZrO 2 , used to provide the doped metal as Y, the specific implementation method is as follows:
[0039] For Y in HfO 2 -ZrO 2 The formation energy of oxygen vacancies in HfO was calculated. When the concentration of Y element and oxygen vacancies was 2:1, the formation energy was negative, indicating that this configuration was more likely to form, indicating the charge balance effect. 2 -ZrO 2The Y element is injected into the film. The results show that the mutual transformation barriers of ot are significantly reduced, and the mutual transformation barriers of the two are similar. In addition, compared with the intrinsic system, the band gap width is slightly reduced, but no deep energy level defects appear. In this embodiment, Y is used as HfO 2 -ZrO 2 Doping with metal can reduce the ot phase transition barrier, thereby promoting the formation of more MPB regions. Secondly, the charge balance effect passivates the defect states caused by oxygen vacancies, achieving a larger band gap and reducing the leakage current, confirming that Y doping can significantly promote the formation of MPB and reduce the leakage current.
[0040] Example 6
[0041] In this embodiment, the superlattice ferroelectric thin film is HfO 2 -ZrO 2 , used to provide the doped metal as La, the specific implementation method is as follows:
[0042] For La in HfO 2 -ZrO 2 The formation energy of oxygen vacancies in HfO was calculated. When the concentration of La element and oxygen vacancies was 2:1, the formation energy was negative, indicating that this configuration was more likely to form, indicating the charge balance effect. 2 -ZrO 2 La is injected into the film. The results show that the mutual transformation barriers of ot are reduced, and the barrier of the transformation of o phase to t phase is greater than that of the transformation of t phase to o phase. In addition, compared with the intrinsic system, the band gap width is slightly reduced, but no deep energy level defects appear. In this embodiment, La is used as HfO 2 -ZrO 2 Doping with metal can reduce the ot phase transition barrier, thereby promoting the formation of more MPB regions. Secondly, the charge balance effect passivates the defect states caused by oxygen vacancies, achieving a larger band gap and reducing the leakage current, confirming that La doping can significantly promote the formation of MPB and reduce the leakage current.
[0043] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A doping modification method for a hafnium oxide-based dielectric film, characterized in that: include: The Zr-layer is doped and modified in the hafnium-based stacking system. On the one hand, the leakage is suppressed by utilizing the restricted oxygen vacancy migration and charge balance effect in the stacking system. On the other hand, the transition barrier between the polarized o phase and the non-polarized t phase is reduced by doping, thus obtaining a hafnium-based stacking system under 3D integration.
2. The doping modification method of hafnium oxide-based dielectric film according to claim 1, characterized in that: The hafnium oxide-based dielectric film is a hafnium-based stacked layer system, and the film thickness is 4-10 nm; wherein the thickness of the HfO2 layer and the ZrO2 layer are both 0.5-2 nm.
3. The doping modification method of hafnium oxide-based dielectric film according to claim 1, characterized in that: The doping position of the doping element is the Zr-layer of the stacked layer system.
4. The doping modification method of hafnium oxide-based dielectric film according to claim 1, characterized in that: The doping element is selected from one or more of Al, Ga, In, Sc, Y, La, Mg, Ca, and Sr.
5. The doping modification method of hafnium oxide-based dielectric film according to claim 4, characterized in that: The doping element is selected from one or more of Al, Y, La, and Sr.
6. The doping modification method of hafnium oxide-based dielectric film according to claim 5, characterized in that: The doping element is Y.
7. The doping modification method of hafnium oxide-based dielectric film according to claim 1, characterized in that: The doping concentration of the doping element is 2%-8%.
Citation Information
Patent Citations
Preparation method of dielectric film and device with ultrahigh dielectric constant and / or ferroelectric remanent polarization and device
CN115497924A
High-transmission low-electric-leakage high-dielectric-constant composite film and preparation and application thereof
CN118471686A
Auto defog sensor
KR102945173B1